The Bridge From Analogue To Digital: Challenges and tendencies for the digitization of sound archives - Haffner, Albrecth (Cuadernos de Documentación Multimedia, 2018)
The Bridge From Analogue To Digital: Challenges and tendencies for the digitization of sound archives